Firm efficiency in selected developed and developing East Asia countries: using data envelopment analysis - Tan, Khar Mang; Kamarudin, Fakarudin; Amin Noordin, Bany Ariffin; Abdul Rahim, Norhuda (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Drawing on the significance of firm efficiency in attaining the primary firms’ goal of profit maximization, the paper aims to examine the firm efficiency or technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) level in the selected East Asia countries during the period of 2009-2015, by employing the non-parametric Data Envelopment Analysis (DEA) based on the production approach. The efficiency level of firms in selected East Asia countries is found to be moderate, by experiencing the mean TE of 53.40per cent with input waste of 46.60per cent during the years 2009-2015. The paper find that the scale inefficiency (SIE) is the dominant source of inefficiency of firms. Furthermore, the paper reveals that the large firms are generally showed decreasing return to scale (DRS); while the small firms are commonly exhibited increasing return to scale (IRS). Finally, the paper concludes that the firms in selected developed countries are found to exhibit higher mean TE than those firms in selected developing countries.